2016
DOI: 10.4337/ejeep.2016.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of wealth inequality in euro area countries: the effect of inheritance and gifts on household gross and net wealth distribution analysed by applying the Shapley value approach to decomposition*

Abstract: This paper investigates the sources of inequality in household gross and net wealth across eight euro area countries applying the Shapley value approach to decomposition. The research draws on micro data from the Eurosystem Household Finance and Consumption Survey 2010. Dispersion in bequests and inter vivos transfers obtained by households are found to have a remarkable effect on wealth inequality that is stronger than that of income differences. In Austria, Germany and Cyprus the contribution of real and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
(40 reference statements)
1
7
0
2
Order By: Relevance
“…Transfers of wealth ( T t ) comprise inheritances and inter‐vivo transfers, as well as asset separation upon divorce. Inheritances are a key factor in explaining wealth inequality (Bowles and Gintis, ; Piketty et al ., ), a fact which is also observed in the European HFCS data used in this analysis (Fessler and Schürz, ; Leitner, ). The distribution of inheritances has also become more unequal over time (Piketty, ).…”
Section: Gender Differences In Wealth Accumulationsupporting
confidence: 74%
See 2 more Smart Citations
“…Transfers of wealth ( T t ) comprise inheritances and inter‐vivo transfers, as well as asset separation upon divorce. Inheritances are a key factor in explaining wealth inequality (Bowles and Gintis, ; Piketty et al ., ), a fact which is also observed in the European HFCS data used in this analysis (Fessler and Schürz, ; Leitner, ). The distribution of inheritances has also become more unequal over time (Piketty, ).…”
Section: Gender Differences In Wealth Accumulationsupporting
confidence: 74%
“…Regarding the present value of inheritances, we follow Fessler et al . () and Leitner () in conservatively assuming real value retention; our consumer price index (CPI) data come from the AMECO database (European Commission, ). We use dummy variables to distinguish between large and small inheritances, using the median level of wealth of the respective country as the cut‐off between the two.…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 While some studies have found that inheritances tend to increase wealth inequality (Leitner, 2016, Humer et al 2017, others have found the opposite (Elinder et al 2018, Wolff andGittleman 2015). This lack of consistency reflects the fact that while richer households tend to receive greater inheritance (and other wealth transfers) than poorer households, wealth transfers are actually greater for the poorer as a proportion of their current wealth holdings.…”
Section: _________________________mentioning
confidence: 99%
“…The third type of papers compares national wealth of different countries (e.g. Euro area in Mathä, Porpiglia and Ziegelmeyer, 2017 or in Leitner, 2016). From the literature review it is clear, that this topic is important and there is a rising pressure on availability of greater amount of better and more reliable data all over the world.…”
Section: Introductionmentioning
confidence: 99%